Validity of Secretin Stimulation Testing on Proton Pump Inhibitor Therapy for Diagnosis of Zollinger-Ellison Syndrome. (13th November 2021) - Bhattacharya, Sumona; Blau, Jenny E.; Cochran, Craig; Auh, Sungyoung; Weinstein, Lee S.; Jensen, Robert T.; Wank, Stephen
Abstract : INTRODUCTION: Zollinger-Ellison syndrome (ZES) is characterized by gastrinoma-induced hypergastrinemia causing excessive gastric acid secretion. Secretin stimulation tests (SSTs) are required for diagnosis in the majority of patients. Two case reports suggest that proton pump inhibitors (PPIs) cause false SST results. Consequently, PPIs are discontinued to allow hyperchlorhydria to recur; however, uncontrolled acidity can cause life-threatening complications in those with underlying undiagnosed ZES. The aim of this study was to determine whether PPIs influence the validity of SSTs for the diagnosis of ZES. METHODS: A retrospective chart review was performed. Charts of patients who underwent SSTs were reviewed to determine whether they were performed on or off PPI and the test's accuracy by comparing the results with gold standard tests (diagnostic laboratory testing performed off PPI or surgical pathology consistent with gastrinoma). Sensitivity, specificity, and positive predictive value (PPV) of SST on PPI were calculated and results compared with SST off PPI using noninferiority analyses. RESULTS: Twenty-eight patients corresponding to 29 SSTs were performed on PPI, and 70 patients corresponding to 107 SSTs were performed off PPI. Most of them were female and white and had multiple endocrine neoplasia type 1. We found no false-positive or false-negative SSTs on PPI. Sensitivity, specificity, and PPV of SSTs on PPI were determined to be noninferior to SSTs off PPI ( P ≤ 0.05 for all). DISCUSSION: In our cohort, SSTs on PPI compared with SSTs off PPI were noninferior for sensitivity, specificity, and PPV. These results suggest that PPI withdrawal before SSTs may not be necessary. Abstract :